2019
DOI: 10.1016/j.jpubeco.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Job search requirements, effort provision and labor market outcomes

Abstract: How effective are effort targets? This paper provides novel evidence on the effects of job search requirements on effort provision and labor market outcomes. Based on large-scale register data, we estimate the returns to required job search effort, instrumenting individual requirements with caseworker stringency. Identification is ensured by the conditional random assignment of job seekers to caseworkers. We find that the duration of un-and non-employment both decrease by 3% if the requirement increases by one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Faberman and Kudlyak (2019) use high-frequency data on individuals' application activity from a U.S. job vacancy website and find a decline in search effort over the course of the unemployment spell. Last, Arni and Schiprowski (2019) use Swiss administrative data to show that requirement-induced effort changes have a meaningful impact on job finding. We add to theses insights by providing evidence on the relationship between the PBD, initial search effort and re-employment outcomes.…”
mentioning
confidence: 99%
“…Faberman and Kudlyak (2019) use high-frequency data on individuals' application activity from a U.S. job vacancy website and find a decline in search effort over the course of the unemployment spell. Last, Arni and Schiprowski (2019) use Swiss administrative data to show that requirement-induced effort changes have a meaningful impact on job finding. We add to theses insights by providing evidence on the relationship between the PBD, initial search effort and re-employment outcomes.…”
mentioning
confidence: 99%
“…Unfortunately, the sample of treated observations in this study is too small to obtain meaningful estimates of differential effects across these variables. However, a growing literature on search requirements and monitoring show that these policies have measurable impacts on UI claiming and durations (Arni & Schiprowski, 2019; Borland & Tseng, 2007; Johnson & Klepinger, 1994; Klepinger et al, 2002; McVicar, 2008; McVicar, 2010; Petrongolo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the observed accepted wages, it can therefore not be concluded that lower reservation wages were an important mechanism in the increased exit rates due to the abolishing of job search requirements for the older unemployed. A study of prime-age workers in Switzerland also finds no effect of job search requirements on accepted wages, but the authors do find a very small negative effect (-0.3%) on the duration of re-employment spells [5].…”
Section: Hans Bloemen | Job Search Requirements For Older Unemployed ...mentioning
confidence: 93%
“…While previous studies ([1], [7]) measure job search requirements based on a policy change that increases search requirements, another study uses variation in search requirements set at the individual level by individual case workers, exploiting administrative data on unemployment inflow in the period 2010-2014 for Switzerland [5]. This study focuses on prime-age workers, rather than older workers.…”
Section: Global Empirical Evidence On Search Requirements For the Une...mentioning
confidence: 99%